Transient alpha-helix in the N-terminal RNA recognition motif of polypyrimidine tract binding protein senses RNA secondary structure - Maris, Christophe; Jayne, Sandrine; Damberger, Fred F.; Beusch, Irene; Dorn, Georg; Ravindranathan, Sapna; Allain, Frederic H-T (Nucleic Acids Research, 2020)
The polypyrimidine tract binding protein (PTB) is a multi-domain protein involved in alternative splicing, mRNA localization, stabilization, polyadenylation and translation initiation from internal ribosome entry sites (IRES). In this latter process, PTB promotes viral translation by interacting extensively with complex structured regions in the 5'-untranslated regions of viral RNAs at pyrimidine-rich targets located in single strand and hairpin regions. To better understand how PTB recognizes structured elements in RNA targets, we solved the solution structure of the N-terminal RNA recognition motif (RRM) in complex with an RNA hairpin embedding the loop sequence UCUUU, which is frequently found in IRESs of the picornovirus family. Surprisingly, a new three-turn alpha 3 helix C-terminal to the RRM, folds upon binding the RNA hairpin. Although alpha 3 does not mediate any contacts to the RNA, it acts as a sensor of RNA secondary structure, suggesting a role for RRM1 in detecting pyrimidine tracts in the context of structured RNA. Moreover, the degree of helix formation depends on the RNA loop sequence. Finally, we show that the alpha 3 helix region, which is highly conserved in vertebrates, is crucial for PTB function in enhancing Encephalomyocarditis virus IRES activity.